Revisiting the ICHD-3 criteria for headache attributed to mild traumatic injury to the head: Insights from the Toronto Concussion Study Analysis of Acute Headaches Following Concussion. (October 2022) - Langer, Laura Kathleen; Bayley, Mark Theodore; Lawrence, David Wyndham; Comper, Paul; Kam, Alice; Tam, Alan; Saverino, Cristina; Wiseman-Hakes, Catherine; Ruttan, Lesley; Chandra, Tharshini; Foster, Evan; Gladstone, Jonathan
Abstract: Background: There is limited prospective data on the prevalence, timing of onset, and characteristics of acute headache following concussion/mild traumatic brain injury. Methods: Adults diagnosed with concussion (arising from injuries not related to work or motor vehicle accidents) were recruited from emergency departments and seen within one week post injury wherein they completed questionnaires assessing demographic variables, pre-injury headache history, post-injury headache history, and the Sport Concussion Assessment Tool (SCAT-3) symptom checklist, the Sleep and Concussion Questionnaire (SCQ) and mood/anxiety on the Brief Symptom Inventory (BSI). Results: A total of 302 participants (59% female) were enrolled (mean age 33.6 years) and almost all (92%) endorsed post-traumatic headache (PTH) with 94% endorsing headache onset within 24 hours of injury. Headache location was not correlated with site of injury. Most participants (84%) experienced daily headache. Headache quality was pressure/squeezing in 69% and throbbing/pulsing type in 22%. Associated symptoms included: photophobia (74%), phonophobia (72%) and nausea (55%). SCAT-3 symptom scores, Brief Symptom Inventory and Sleep and Concussion Questionnaire scores were significantly higher in those endorsing acute PTH. No significant differences were found in week 1 acute PTH by sex, history of migraine, pre-injury headache frequency, anxiety, or depression, nor presence/absence of post-traumatic amnesia and self-reported loss of consciousness. Conclusions: This study highlights the very high incidence of acute PTH following concussion, the timing of onset and characteristics of acute PTH, the associated psychological and sleep disturbances and notes that the current ICHD-3 criteria for headaches attributed to mild traumatic injury to the head are reasonable, the interval between injury and headache onset should not be extended beyond seven days and could, potentially, be shorted to allow for greater diagnostic precision.